Jogos e simulações para ensino de conceitos enxutos: mapeamento sistemático da literatura - Viana, Marina Ribeiro; Santos, Paulo Ricardo Ramos; Santos, Débora de Gois; Lima, Renan Tenório de Araújo (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Civil construction management seeks to analyze the processes in order to optimize them. One way to accomplish this is from the implementation of lean thinking aiming to reduce or eliminate activities that do not add value to the product. In this scenario, it is necessary to disseminate the lean concepts among the current and future professionals of the sector. In this respect, it is understood that games can be an efficient pedagogical asset while they stimulate participation and motivating those involved in the learning process. This paper aimed, through a quantitative approach, to select and analyze a bibliographic portfolio about the topic of the games use for teaching lean construction concepts, so identifying a knowledge gap in this area. For this, it used the ProKnow-C method (Afonso et al., 2011; Vilela, 2012) for publication selection and their bibliometric analysis. As a result, it was formed a bibliographic portfolio about the researched topic. Thus, it was possible to quantify the most cited authors, the most recurrent keywords, as well as the publication distribution along the time. Finally, it was observed that research matching gamification and teaching of lean concepts are scarce, indicating a knowledge gap to be filled.